3-(4-Chlorobenzoyl)-4-(4-chlorophenyl)-1-phenethylpiperidin-4-ol - Aydin, Abdullah; Gül, Halise İnci; Akkurt, Mehmet; Mete, Ebru; Şahi̇n, Ertan (International Union of Crystallography (IUCr), 2011)
In the title compound, C(26)H(25)Cl(2)NO(2), the piperidine ring adopts a chair conformation with a cis configuration of the carbonyl and hy-droxy substituents. The dihedral angle between the aromatic rings of the chloro-benzene groups is 24.3 (2)°. The phenyl ring forms dihedral angles of 59.4 (3) and 44.1 (3)° with the benzene rings. In the crystal, mol-ecules are linked by inter-molecular O-H⋯N and C-H⋯O hydrogen bonds and C-H⋯π inter-actions into layers parallel to the bc plane.
Keywords: Crystallography; QD901-999; Organic Papers; 3. Good health